Faltan criterios para escoger árboles de uso urbano - Jímenez Jara, Joaquín (2017)
In Costa Rica there is very little criteria following international norms of quality in the cultivation of trees used in urban forestry. In most developing countries we find a series of rules and characteristics that have to be followed and obey in order to plant trees on public places like parks and roads. Not complyingwith these rules will eventually bring serious consequences to the property and citizens who used these public areas.